Environment-friendly high-strength concrete as well as preparation method and application thereof

By constructing a dense skeleton in concrete and introducing graphene oxide and steel fiber, combined with dry-wet mixing and multi-stage temperature control curing, the problem of synergistically improving the material strength, toughness and environmental performance of high-strength concrete was solved, and efficient and stable component dispersion and performance optimization were achieved.

CN120774672APending Publication Date: 2025-10-14BEIJING MINJIA CONCRETE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510930950.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-07
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

When preparing high-strength concrete with existing technologies, it is difficult to synergistically improve the strength, toughness and environmental performance of the material. The uneven dispersion of functional components leads to unstable performance. The traditional mixing process leads to uneven fiber distribution, and the dispersion of nanomaterials in alkaline environments is seriously difficult.

Method used

A dense skeleton is constructed using quartz sand of different particle sizes, which is then filled step by step with multi-scale cementitious materials. Graphene oxide and steel fiber are introduced, and sequential mixing using dry and wet methods and multi-stage temperature control curing are used to ensure uniform dispersion of components and active activation.

Benefits of technology

It achieves ultra-high density and excellent durability concrete, significantly improves toughness and crack resistance, effectively utilizes industrial solid waste, reduces carbon emissions and ensures stable product quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005486295440000081
    Figure BDA0005486295440000081
  • Figure BDA0005486295440000091
    Figure BDA0005486295440000091
  • Figure BDA0005486295440000101
    Figure BDA0005486295440000101
Patent Text Reader

Abstract

The invention relates to the field of concrete materials, and discloses environment-friendly high-strength concrete as well as a preparation method and application thereof. Coal ash; slag powder; silica fume; coarse quartz sand; fine quartz sand; graphene oxide; steel fibers; lithium carbonate; a high-performance water reducing agent; the particle size range of the coarse quartz sand is 0.30-0.60 mm, the particle size range of the fine quartz sand is 0.15-0.30 mm, the graphene oxide is single-layer graphene oxide powder, the oxygen content range of the graphene oxide powder is 40-50%, the steel fiber is copper-plated steel fiber with a hook-shaped tail end, and the tensile strength of the steel fiber is not lower than 2850 MPa. Through dense stacking design, nano functionalization and sequential stirring processes, the prepared concrete has the advantages of ultrahigh strength, high toughness, high stability and high solid waste mixing amount.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of concrete materials, in particular to an environment-friendly high-strength concrete and a preparation method and application thereof. BACKGROUND

[0002] With the continuous development of modern civil engineering, there is an increasing demand for building materials with ultra-high strength, excellent durability and outstanding toughness to meet the stringent requirements of large-span structures, super high-rise buildings and special protective engineering. At the same time, under the trend of global sustainable development, the development of green and low-carbon concrete materials by utilizing industrial solid waste has become a crucial research direction in the industry.

[0003] To obtain high-strength concrete, the existing technical solutions usually focus on reducing the water-binder ratio and compounding high-performance water reducing agents to ensure their workability. At the same time, in order to improve the density of cement stone and enhance long-term strength, mineral admixtures such as silica fume, fly ash and slag powder are generally added to partially replace cement. In some cases, steel fibers or synthetic fibers are directly added to the mixture to improve the toughness of the material. The preparation process usually involves putting all solid and liquid components into a mixer for one-step mixing to prepare a concrete mixture.

[0004] Although the existing technology has achieved certain results in improving the strength of concrete, there are still some deficiencies: the traditional design concept only regards aggregates as fillers, which fundamentally limits the packing density of the system, resulting in an upper limit for the improvement of its strength and durability. In addition, the early activity of industrial solid waste such as fly ash and slag powder is low under conventional curing conditions, and the high dosage application often sacrifices the early strength of concrete, causing a contradiction between environmental benefits and engineering needs. When trying to introduce steel fibers and other reinforcing components, the conventional one-step mixing process is prone to cause fiber aggregation and uneven distribution, making it difficult to achieve stable and effective toughening effect. Similarly, when advanced nanomaterials are introduced to further improve performance, the serious dispersion problem in the alkaline cement environment often makes it not only unable to bring the expected performance gain, but also easily deteriorates the workability and uniformity of the material. SUMMARY

[0005] The purpose of the present application is to provide an environment-friendly high-strength concrete and a preparation method and application thereof, which solves the problem that the strength, toughness and environmental performance of the material are difficult to be synergistically improved due to the limitations of design concept and preparation process in the prior art when preparing high-strength concrete, and the uneven dispersion of functional components leads to unstable performance.

[0006] To achieve the above purpose, the present application is implemented by the following technical solutions: According to a first aspect of the present application, there is provided an environmentally friendly high-strength concrete, comprising the following components in parts by weight: Portland cement: 300-400 parts; Fly ash: 150-200 parts; GGBFS: 200-250 parts; Silica fume: 50-80 parts; Coarse quartz sand: 500-700 parts; Fine quartz sand: 400-500 parts; The present application regards high-hardness and stable-performance quartz sand as the "structural framework" of the material. Through scientific grading of two different particle sizes of quartz sand, a low-porosity packing system is first formed on a macro scale. Subsequently, cement, fly ash, GGBFS and other composite cementitious materials with smaller particle sizes serve as "fillers" to fill the micron-level gaps between the quartz sand framework. Smaller silica fume further fills the sub-micron-level gaps between the cementitious material particles. The purpose of such additives is to physically construct a solid particle bed before adding water, thereby minimizing the original gap volume inside the system that needs to be filled by hydration products.

[0007] Graphene oxide: 0.08-0.45 parts; Steel fiber: 8-28 parts; Lithium carbonate: 0.8-4.6 parts; High-performance water reducing agent: 4-14 parts; Mixing water: 176-260 parts.

[0008] In the present application, the introduction of graphene oxide as a nanofiller has a heterogeneous nucleation effect as a "seed". During the subsequent hydration reaction, uniformly dispersed graphene oxide nanosheets can provide a large number of high-activity nucleation sites for hydration products, guiding them to form finer and denser crystal structures, thereby optimizing the microstructure of the cement paste from a nanoscale perspective. By adding steel fibers, when micro-cracks occur in the concrete matrix, the steel fibers consume a large amount of energy through their own stretching and pulling out, effectively inhibiting the propagation of cracks, thereby imparting excellent toughness and impact resistance to the material. Lithium carbonate as a chemical activity regulator can catalyze the early hydration reaction of Portland cement.

[0009] Preferably, the particle size range of the coarse quartz sand is 0.30-0.60 mm, and the particle size range of the fine quartz sand is 0.15-0.30 mm.

[0010] Preferably, the graphene oxide is single-layer graphene oxide powder with an oxygen content range of 40-50%.

[0011] Preferably, the steel fiber is a copper-plated steel fiber with a terminal hook, and the tensile strength thereof is not less than 2850 MPa.

[0012] According to a second aspect of the present application, a preparation method of the environment-friendly high-strength concrete is provided for preparing the above concrete, and the method comprises the following steps: S1, preparing a nano-functionalized suspension; S2, performing dry-wet sequential stirring; S3, performing multi-stage temperature control curing.

[0013] Preferably, in the step S1, the step of preparing the nano-functionalized suspension comprises: mixing graphene oxide, lithium carbonate, a high-performance water reducing agent, and water for mixing; adjusting the pH value of the mixed solution to a range of 9.0-11.0 using a pH adjuster; performing ultrasonic treatment on the mixed solution to obtain a nano-functionalized suspension, wherein the ultrasonic treatment parameters are as follows: the ultrasonic frequency is 20-25 kHz, the output power is 500-800 W, the treatment time is 15-30 minutes, and the temperature is controlled within a range of 15-40℃ during the treatment.

[0014] By pre-mixing graphene oxide with a water reducing agent, lithium carbonate, and the like, and performing pH regulation and ultrasonic treatment thereon, the graphene oxide powder is reduced and stabilized into a single-layer or few-layer nano-sheets dispersion liquid with functional groups by using chemical means (pH regulation to stabilize surface charge) and physical energy (ultrasonic cavitation effect to peel off the sheets). Thus, the graphene oxide can be introduced into the concrete system in the most effective dispersion state.

[0015] Preferably, in the step S2, the stirring operation is performed in a planetary concrete mixer, and specifically comprises: dry mixing cement, fly ash, slag powder, silica fume, coarse quartz sand, and fine quartz sand at a rotation speed of 55-65 rpm for 3-5 minutes; adding steel fibers, and continuing to stir at a rotation speed of 55-60 rpm for 1-2 minutes; adding the nano-functionalized suspension, and then high-speed stirring at a rotation speed of 110-130 rpm for 3-5 minutes.

[0016] First, all the solid powders and aggregates are dry mixed for a long time, in order to achieve the maximum statistical uniformity of all the micron and millimeter particles before adding water, forming a homogeneous "reaction bed". Then, steel fibers are mixed in a dry state, using the spacing effect of the powder to physically disperse the steel fibers, preventing them from clumping together due to surface tension after adding water. Finally, the pre-prepared nanofunctional suspension is added and stirred at high speed, ensuring that every solid particle and every steel fiber is uniformly wetted and coated by the functional liquid phase, laying the foundation for forming strong and uniform interfacial bonding strength.

[0017] Preferably, in the step S3, the multi-stage temperature control curing step includes two stages of curing operation.

[0018] Preferably, in the step S3, the two stages of curing operation include: The first stage of normal temperature initial curing, which is to cure the formed concrete mixture in an environment with a temperature of 28-22℃ and a relative humidity of not less than 95% for 23-25 hours; The second stage of high temperature accelerated curing, which is to heat the concrete to a constant temperature of 60-80℃ at a heating rate of 15-25℃ / hour and maintain the temperature for 46-50 hours.

[0019] The first stage of normal temperature curing is to use the catalytic effect of lithium carbonate to quickly hydrate the cement components with the highest reaction activity, forming an initial skeleton that can support the structure and stabilize the form. The subsequent second stage of high temperature accelerated curing provides the activation energy necessary for the secondary pozzolanic reaction of fly ash and slag powder with lower reaction activity in a high temperature environment, promoting them to fully react with calcium hydroxide produced by early hydration of cement to generate a large amount of additional hydrated calcium silicate gel that can fill the pores, filling all the remaining small pores after the first stage and achieving the ultimate densification of the internal structure of the concrete, thereby enhancing the strength of the concrete.

[0020] According to a third aspect of the present application, the use of the above-mentioned environmentally friendly high-strength concrete or the above-mentioned preparation method in the preparation of prefabricated building components, 3D printed buildings or special engineering structures is provided.

[0021] In summary, the present application includes at least one of the following beneficial technical effects: 1.The present application designs the composition by adopting the closest packing theory, constructs the dense skeleton with quartz sand of different particle sizes, and then fills it with multi-scale cementing materials and silica fume step by step to physically build an initial system with ultra-high density. Combined with the subsequent multi-stage temperature control curing system, the activity of components such as fly ash and slag powder is fully stimulated, and finally a cement stone matrix with extremely dense microstructure and no obvious defects is formed, thereby giving the concrete a compressive strength far exceeding that of conventional materials and excellent durability.

[0022] 2.The present application significantly improves the toughness and crack resistance of the material by introducing steel fibers into the dense matrix and ensuring their uniform dispersion by using dry-wet sequential mixing process. When microcracks appear in the matrix, the uniformly distributed steel fibers can effectively play a "bridging" role, inhibit the propagation of cracks and absorb a large amount of energy, making the material exhibit excellent bending capacity and fracture toughness, thereby greatly improving the structural reliability and safety of the product.

[0023] 3.The present application uses quartz sand as the skeleton and a large amount of fly ash, slag powder and other industrial by-products to replace cement with high energy consumption and high carbon emission. Through a unique multi-stage temperature control curing process, the chemical activity of these industrial solid wastes is effectively activated, realizing their high-value resource utilization. This not only greatly reduces the cement consumption of unit strength concrete, reduces the consumption of natural resources and carbon emissions, but also provides a new and effective way for the utilization of industrial solid wastes.

[0024] 4.The present application fundamentally solves the technical problem of easy agglomeration of nanomaterials in the cement system by preparing graphene oxide into a nanofunctional suspension in advance, ensuring the flowability of the mixture. The unique sequential mixing process ensures the highly uniform distribution of each component, especially steel fibers, so that the mechanical properties of the final product have little dispersion, the product quality is stable and reliable, and it has strong engineering application value. DETAILED DESCRIPTION

[0025] The present application will be further described in detail below in conjunction with Examples 1-3.

[0026] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0027] Example 1: The present application provides an environmentally friendly high-strength concrete, which comprises the following components in parts by weight: portland cement: 350 parts; fly ash: 175 parts; slag powder: 225 parts; silica fume: 65 parts; coarse quartz sand: 600 parts; fine quartz sand: 450 parts; graphene oxide: 0.26 parts; steel fiber: 18 parts; lithium carbonate: 2.7 parts; high-performance water reducing agent: 9 parts; mixing water: 218 parts. Among them, the particle size of the coarse quartz sand is 0.45 mm, the particle size of the fine quartz sand is 0.22 mm, the graphene oxide is a single-layer powder with an oxygen element content of 45%, and the steel fiber is a terminal hook type copper-plated steel fiber.

[0028] The preparation method of the concrete is as follows: S1, preparing a nano-functionalized suspension: 0.26 parts of graphene oxide, 2.7 parts of lithium carbonate, 9 parts of high-performance water reducing agent and 218 parts of mixing water are placed in a beaker and mixed; a sodium hydroxide solution with a concentration of 0.1 mol / L is used as a pH adjuster to accurately adjust the pH value of the mixed solution to 10.0; then the mixed solution is transferred to a container with a cooling water circulation, and a probe-type ultrasonic processor is used for processing, with the processing parameters set as: ultrasonic frequency 22 kHz, output power 650 W, processing time 22 minutes, and the temperature of the suspension is controlled at 25℃ throughout the process by circulating water.

[0029] S2, performing dry-wet sequential mixing: in a planetary concrete mixer, 350 parts of portland cement, 175 parts of fly ash, 225 parts of slag powder, 65 parts of silica fume, 600 parts of coarse quartz sand and 450 parts of fine quartz sand are put into the mixer and dry mixed at a speed of 60 rpm for 4 minutes; then, 18 parts of steel fiber are added and the stirring speed is increased to 58 rpm for 1.5 minutes; finally, all the nano-functionalized suspension prepared in step S1 is added into the mixer and stirred at a high speed of 120 rpm for 4 minutes to obtain a uniform concrete mixture.

[0030] S3, performing multi-stage temperature-controlled curing: after the mixture is poured and formed, the first stage of normal temperature initial curing is immediately performed, with the condition being: curing in a standard curing room with a temperature of 25℃ and a relative humidity of not less than 95% for 24 hours; then demolding and performing the second stage of high-temperature accelerated curing, with the condition being: heating the test piece to a constant temperature of 70℃ at a heating rate of 20℃ / hour, and curing at this temperature for 48 hours, and then cooling to room temperature with the furnace.

[0031] Example 2: The present application provides an environment-friendly high-strength concrete, which comprises the following components in parts by weight: Portland cement: 300 parts; fly ash: 150 parts; slag powder: 200 parts; silica fume: 50 parts; coarse quartz sand: 500 parts; fine quartz sand: 400 parts; graphene oxide: 0.08 parts; steel fiber: 8 parts; lithium carbonate: 0.8 parts; high-performance water reducing agent: 4 parts; mixing water: 176 parts. Among them, the particle size of coarse quartz sand is 0.30 millimeter, the particle size of fine quartz sand is 0.15 millimeter, the graphene oxide is a single-layer powder with an oxygen content of 40%, and the steel fiber is a terminal hook type copper-plated steel fiber.

[0032] The preparation method of the concrete is as follows: S1, preparing a nano-functionalized suspension: mixing 0.08 parts of graphene oxide, 0.8 parts of lithium carbonate, 4 parts of high-performance water reducing agent, and 176 parts of mixing water; using a pH adjuster to adjust the pH value of the mixed solution to 9.0; then performing ultrasonic treatment, with the parameters set as: ultrasonic frequency 20 kHz, output power 500 W, treatment time 15 minutes, and the temperature during the treatment controlled at 15℃.

[0033] S2, performing dry-wet sequential stirring: in a planetary concrete mixer, all the powdered components and sand are put in for dry mixing at a speed of 55 rpm for 3 minutes; then, 8 parts of steel fiber are added, and the stirring is continued at a speed of 55 rpm for 1 minute; finally, the suspension prepared in step S1 is added, and high-speed stirring is performed at a speed of 110 rpm for 3 minutes to obtain a concrete mixture.

[0034] S3, performing multi-stage temperature-controlled curing: after the mixture is formed, the first-stage normal-temperature initial curing is performed under the condition that the temperature is 22℃ and the relative humidity is not less than 95%, for 23 hours; then the second-stage high-temperature accelerated curing is performed under the condition that the concrete is heated to 60℃ at a heating rate of 15℃ / hour, and cured at this temperature for 46 hours, and then naturally cooled.

[0035] Example 3: The present application provides an environmentally friendly high-strength concrete, which comprises the following components in parts by weight: Portland cement: 400 parts; fly ash: 200 parts; slag powder: 250 parts; silica fume: 80 parts; coarse quartz sand: 700 parts; fine quartz sand: 500 parts; graphene oxide: 0.45 parts; steel fiber: 28 parts; lithium carbonate: 4.6 parts; high-performance water reducing agent: 14 parts; mixing water: 260 parts. Among them, the particle size of coarse quartz sand is 0.60 millimeter, the particle size of fine quartz sand is 0.30 millimeter, the graphene oxide is a single-layer powder with an oxygen content of 50%, and the steel fiber is a terminal hook type copper-plated steel fiber.

[0036] The preparation method of the concrete is as follows: S1, Preparation of nano-functionalized suspension: 0.45 parts of graphene oxide, 4.6 parts of lithium carbonate, 14 parts of high-performance water-reducing agent, and 260 parts of mixing water were mixed; a pH adjuster was used to adjust the pH value of the mixture to 11.0; then ultrasonic treatment was performed, with the parameters set as: ultrasonic frequency 25 kHz, output power 800 W, treatment time 30 minutes, and the temperature during the treatment controlled at 40°C.

[0037] S2, Dry-wet sequential mixing: in a planetary concrete mixer, all the powdery components and sand were put in for dry mixing at a speed of 65 rpm for 5 minutes; then, 28 parts of steel fibers were added, and the stirring was continued at a speed of 60 rpm for 2 minutes; finally, the suspension prepared in step S1 was added, and high-speed stirring was performed at a speed of 130 rpm for 5 minutes to obtain a concrete mixture.

[0038] S3, Multi-stage temperature-controlled curing: after the mixture was formed, the first stage of normal temperature initial curing was performed under the condition of a temperature of 28°C and a relative humidity of not less than 95% for 25 hours; then, the second stage of high-temperature accelerated curing was performed by increasing the temperature of the concrete to 80°C at a rate of 25°C / hour, and curing at this temperature for 50 hours, followed by forced air cooling.

[0039] Comparative Example 1: Compared with Example 1, the difference lies in that instead of using two different particle sizes of quartz sand for grading, a single grade of quartz sand with a total weight of 1050 parts and a particle size range of 0.15-0.60 mm is used, and the rest is the same.

[0040] Comparative Example 2: Compared with Example 1, the difference lies in that the graphene oxide component is not added to the composition, and in step S1 of the preparation method, the operation related to graphene oxide is also not performed, and the rest is the same.

[0041] Comparative Example 3: Compared with Example 1, the difference lies in that the lithium carbonate component is not added to the composition, and in step S1 of the preparation method, the operation related to lithium carbonate is also not performed, and the rest is the same.

[0042] Comparative Example 4: Compared with Example 1, the difference lies in that the steel fiber component is not added to the composition, and in step S2 of the preparation method, the sub-step of adding steel fibers and stirring is omitted, and the rest is the same.

[0043] Comparative Example 5: Compared with Example 1, the difference lies in that the entire operation of step S1 in the preparation method is omitted. Instead, in the wet mixing stage of step S2, the graphene oxide powder, lithium carbonate, high-performance water-reducing agent, and mixing water are directly added to the mixer together with other solid powders for mixing, and the rest is the same.

[0044] Comparative Example 6: Compared with Example 1, the difference is that step S2 in the preparation method is replaced by a traditional one-step feeding method. The alternative method is: all solid-liquid components in the formula of Example 1 are put into a planetary mixer at one time, and directly stirred at a speed of 120 rpm for 5 minutes, and the rest are the same.

[0045] Comparative Example 7: Compared with Example 1, the difference is that the second stage in step S3 in the preparation method is omitted. The alternative method is: the formed concrete mixture is continuously cured in a standard curing room with a temperature of 25°C and a relative humidity of not less than 95% to the specified age, and the rest are the same.

[0046] Test Example 1: Experimental Steps: Preparation of Test Pieces and Grouping: According to the formula and preparation method of the preceding Example 1 and Comparative Examples 1, 2, 3, and 4, five groups of concrete mixtures were prepared.

[0047] For each group of mixtures, immediately sample for flow test in step 2.

[0048] Pour the remaining mixtures into molds. Each group makes: Cubic test blocks with a size of 100mm x 100mm x 100mm, a total of 6 blocks, for compressive strength testing.

[0049] Prism test blocks with a size of 100mm x 100mm x 400mm, a total of 3 blocks, for flexural strength and fracture toughness testing.

[0050] All test pieces are cured according to the "multi-stage temperature control curing" system of Example 1 until the specified test age is reached.

[0051] Test Method for Mixture Flow: Fill the mixture into a standard slump cone, after lifting the bucket, wait for the mixture to stop flowing, measure the diameters of the two perpendicular directions of the expanded circular paste, and take the average value as the flow value of the mixture in this group.

[0052] Compressive Strength Test: Test Method: At the 3-day curing age, 3 cubic test pieces were taken out for testing.

[0053] At the 28-day curing age, another 3 cubic test pieces were taken out for testing.

[0054] Place the test pieces on a 3000kN electro-hydraulic servo pressure testing machine, continuously load at a loading rate of 0.5MPa / s until the test piece fails, record the peak load, and calculate the compressive strength. The average value of 3 test pieces in each group is taken as the final result.

[0055] Flexural strength test: Test method: At the age of 28 days, the prism test block was taken out and tested by four-point bending method. The test block was placed on the universal testing machine, and the load was applied at a rate of 50 N / s until the test block was broken. The peak load was recorded, and the flexural strength was calculated.

[0056] Fracture toughness test: Test method: At the age of 28 days, a notch was pre-prepared in the middle of the remaining prism test block to form a single-edge notched beam. The three-point bending method was used to load the universal testing machine at a displacement control rate of 0.05 mm / min. The load-displacement curve during the entire loading process was recorded, and the fracture toughness of the material was calculated. The test results are shown in Table 1.

[0057] Table 1 Test results of composition system integrity verification From Table 1, it can be seen that: Example 1 showed comprehensive advantages in various performance indicators as a complete system. In comparison, Comparative Example 1 used single-sized quartz sand, which destroyed the initial skeleton accumulation model from millimeter to sub-millimeter designed in the present application, resulting in an increase in the original void ratio between particles, which directly reflected the decrease in the flowability of the mixture and the reduction in the final 28-day compressive strength.

[0058] In Comparative Example 3, the lithium carbonate was removed, and the 3-day early strength dropped sharply, which confirmed that lithium carbonate, as an effective catalyst for early hydration reaction, played an irreplaceable role in ensuring the rapid formation of the initial strength skeleton of concrete. In Comparative Example 2, the absence of graphene oxide did not significantly affect the early strength, but resulted in a significant drop in the 28-day compressive and flexural strength.

[0059] In Comparative Example 4, after removing the steel fibers, the compressive strength did not change compared to Example 1, but the flexural strength and fracture toughness values decreased by an order of magnitude. This result precisely confirmed the core mechanism of steel fibers in the present system, i.e., "crack bridging". It consumes a large amount of energy through its own stretching and pulling out when the matrix cracks, effectively inhibiting the propagation of cracks, thereby imparting excellent toughness and bending resistance to the material.

[0060] Test Example 2: Experimental steps: Preparation of test pieces and grouping: According to the formulations and preparation methods of the aforementioned Example 1 and Comparative Examples 5, 6, and 7, four groups of concrete mixtures were prepared.

[0061] For each group of mixtures, immediately sample for flowability test in Step 2.

[0062] Pour the rest of the mixtures into the mold. Each group is made of: Cubic test blocks with a size of 100mm x 100mm x 100mm, a total of 6, for 28-day compressive strength test.

[0063] Prism test blocks with a size of 100mm x 100mm x 400mm, a total of 6, for 28-day flexural strength test.

[0064] Except for the test blocks of Comparative Example 7 which are continuously cured in the standard curing room, the test blocks of the rest of the groups are cured according to the "Multi-stage temperature control curing" system of Example 1 until the 28-day test age is reached.

[0065] Mixtures flowability test: Test method: Fill the standard slump cone with the mixture, after lifting the bucket, wait for the mixture to stop flowing, measure the diameters of the two mutually perpendicular directions of the expanded circular paste, take the average value as the flowability value of the mixture of this group, which is used to evaluate its workability.

[0066] Mechanical property test and homogeneity evaluation: Compressive strength test: At the age of 28 days of curing, 6 cubic test blocks of each group are taken out, and loaded continuously on a 3000kN electro-hydraulic servo pressure testing machine at a loading rate of 0.5MPa / s until the test block is destroyed. Record the peak load of each block.

[0067] Flexural strength test: At the age of 28 days of curing, 6 prism test blocks of each group are taken out, and loaded on a universal testing machine using the four-point bending method at a loading rate of 50N / s until the test block is broken. Record the peak load of each block.

[0068] Data processing and homogeneity evaluation: Calculate the arithmetic mean of the 6 compressive strength test results and the 6 flexural strength test results of each group, respectively, as the final mechanical property index of the group. At the same time, calculate the standard deviation of the two groups of data, which is used to quantitatively evaluate the dispersion degree of the product performance. The smaller the standard deviation, the better the homogeneity of the material. The test results are shown in Table 2.

[0069] Table 2 Preparation process advancement verification test results From Table 2, we can get: The treatment method of Comparative Example 5, i.e. omitting the pretreatment step of the liquid phase system and directly putting each component into stirring, significantly reduces the fluidity of the mixture, and the final compressive and flexural strength is also greatly reduced. It shows that in the high alkalinity and high ionic concentration environment of cement, untreated graphene oxide and other nanomaterials will undergo irreversible agglomeration, which not only cannot effectively play its "seed" effect and interface enhancement effect, but will become a defect in the system, wrapping water and deteriorating the workability.

[0070] Comparative Example 6 uses the traditional one-step feeding method, although the average strength decreases is not the most severe, but the standard deviation of the compressive and flexural strength results increases several times. This accurately reflects the inherent defect that one-step feeding method cannot guarantee the homogeneity of the microstructure of the material. The sequential stirring process of the present application ensures the macroscopic uniformity of all solid particles before water is added, and effectively disperses the steel fibers using the physical spacing effect of the powder.

[0071] Comparative Example 7 only omits the second stage of high-temperature accelerated curing, and the final 28-day compressive and flexural strength has a cliff-like drop. This proves that the curing system of the present application is not simply "ripening", but "targeted activation" with a clear goal. Normal temperature curing ensures the formation of the initial skeleton, and the subsequent high-temperature stage provides the activation energy necessary for the secondary pozzolanic reaction of fly ash and slag powder with lower reaction activity. Only through high-temperature curing can they fully react with cement hydration products to generate a large amount of additional gel products that can densify the microstructure of the matrix.

[0072] Although embodiments of the present application have been shown and described, it will be understood by those having ordinary skill in the art that various changes, modifications, substitutions and alterations can be made thereto without departing from the principles and spirit of the present application, the scope of which is defined by the appended claims and their equivalents.

Claims

1. An environmentally friendly high-strength concrete, characterized in that: The concrete comprises the following components in parts by weight: Portland cement: 300-400 parts; Fly ash: 150-200 parts; Slag powder: 200-250 parts; Silica fume: 50-80 parts; Coarse quartz sand: 500-700 parts; Fine quartz sand: 400-500 parts; Graphene oxide: 0.08-0.45 parts; Steel fiber: 8-28 parts; Lithium carbonate: 0.8-4.6 parts; High performance water reducer: 4-14 parts; Mixing water: 176-260 parts.

2. The environmentally friendly high-strength concrete according to claim 1, characterized in that: The particle size of the coarse quartz sand is in the range of 0.30-0.60 mm, and the particle size of the fine quartz sand is in the range of 0.15-0.30 mm.

3. The environmentally friendly high-strength concrete according to claim 1, characterized in that: The graphene oxide is a single-layer graphene oxide powder, and its oxygen content ranges from 40% to 50%.

4. The environmentally friendly high-strength concrete according to claim 1, characterized in that: The steel fiber is a copper-plated steel fiber with a hook-shaped end, and its tensile strength is not less than 2850 MPa.

5. A method for preparing environmentally friendly high-strength concrete, for preparing the environmentally friendly high-strength concrete according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, preparing nanofunctional suspension; S2, performing dry and wet sequential stirring; S3. Carry out multi-stage temperature control maintenance.

6. The method for preparing an environmentally friendly high-strength concrete according to claim 5, characterized in that: In step S1, the step of preparing the nano-functionalized suspension includes: Mixing graphene oxide, lithium carbonate, high-performance water reducer and mixing water; Using a pH regulator, the pH value of the mixed solution is adjusted to within the range of 9.0-11.0; The mixed liquid is ultrasonically treated to obtain a nano-functional suspension, wherein the parameters of the ultrasonic treatment are: ultrasonic frequency of 20-25 kHz, output power of 500-800 W, treatment time of 15-30 minutes, and temperature controlled within the range of 15-40° C. during the treatment process.

7. The method for preparing an environmentally friendly high-strength concrete according to claim 5, characterized in that: In step S2, the mixing operation is performed in a planetary concrete mixer, specifically comprising: Dry mix cement, fly ash, slag powder, silica fume, coarse quartz sand and fine quartz sand at 55-65 rpm for 3-5 minutes; Add steel fiber and continue stirring at 55-60 rpm for 1-2 minutes; The nano-functional suspension was added, and then stirred at a high speed of 110-130 rpm for 3-5 minutes.

8. The method for preparing an environmentally friendly high-strength concrete according to claim 5, characterized in that: In step S3, the multi-stage temperature control curing step includes two stages of curing operations.

9. The method for preparing an environmentally friendly high-strength concrete according to claim 5, characterized in that: In step S3, the two-stage curing operation includes: The first stage of normal temperature initial curing is as follows: the formed concrete mixture is cured for 23-25 ​​hours at a temperature of 28-22°C and a relative humidity of not less than 95%; The second stage of high temperature accelerated curing is as follows: the concrete is heated to a constant temperature of 60-80°C at a heating rate of 15-25°C / hour and cured at this temperature for 46-50 hours.

10. Use of the environmentally friendly high-strength concrete according to any one of claims 1 to 4 in the preparation of prefabricated building components, 3D printed buildings or special engineering structures.